Does a Country Need a Promotion Agency to Attract Foreign Direct Investment : A Small Analytical Model Applied to 58 Countries - Morisset, Jacques (World Bank, Washington, DC, 2014)
Establishing an investment promotion agency has become a central part of most countries' development strategies. Today there are more than 150 investment promotion agencies worldwide. Yet very little is known about what these agencies have been really doing, notably in emerging countries, and whether they have been effective in influencing investors' decisions. Using data from a new survey on 58 countries, Morisset shows that greater investment promotion is associated with higher cross-country foreign direct investment (FDI) flows, on top of the influence of the country's investment climate and market size. But this result has to be qualified on several counts. First, the effectiveness of the agency depends on the country's environment in which it operates. An agency in a poor investment climate is less effective at attracting investment. Second, the scope of activities that an agency undertakes influences its performance. Morisset's empirical analysis indicates that agencies devoting more resources on policy advocacy are more effective because such activity is not only beneficial to foreign investors but also to domestic investors. In contrast, investment generation or targeting strategies appear expensive and risky, especially in countries with poor investment climates. Finally, certain internal characteristics of the agencies are associated with greater effectiveness. The agencies that have established reporting mechanisms to the country's highest policymakers (the president or prime minister) or to the private sector have been systematically more efficient at attracting foreign direct investment. Such institutional links are crucial because they contribute to strengthen the government's commitment as well as reinforce the agency's credibility and visibility in the business community.